1999
DOI: 10.1289/ehp.99107385
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitellogenin levels and reproductive impairment of male Japanese Medaka (Oryzias latipes) exposed to 4-tert-octylphenol.

Abstract: The induction of synthesis of the "female" yolk precursor protein vitellogenin (VTG) in male fish by estrogenic chemicals in the environment has been demonstrated in many recent reports. However, little is known about the organismal and biological significance of this phenomenon. To examine the relationship between VTG production in male fish and reproductive impairment, adult male medaka were exposed to 4-tert-octylphenol (OP), a known environmental estrogen, in concentrations ranging ftom 20 to 230 ppb for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(106 citation statements)
references
References 55 publications
5
98
1
1
Order By: Relevance
“…Some xenoestrogens showing both ER agonistic and antagonistic effects had been reported, which also were confirmed that the antagonistic activity of these compounds, although statistically significant, was biologically marginal (Soto et al, 1997). In an in vivo test, the vitellogenin was detected in serum of the male medaka fish exposed to 4-t-OP in all treatment group in steadily increasing concentrations (Gronen et al, 1999), proving the estrogenic activity of 4-t-OP in fish. Endocrine disrupters are widely known for their estrogenic and androgenic effects by binding to ER or AR.…”
Section: Action Sitessupporting
confidence: 65%
“…Some xenoestrogens showing both ER agonistic and antagonistic effects had been reported, which also were confirmed that the antagonistic activity of these compounds, although statistically significant, was biologically marginal (Soto et al, 1997). In an in vivo test, the vitellogenin was detected in serum of the male medaka fish exposed to 4-t-OP in all treatment group in steadily increasing concentrations (Gronen et al, 1999), proving the estrogenic activity of 4-t-OP in fish. Endocrine disrupters are widely known for their estrogenic and androgenic effects by binding to ER or AR.…”
Section: Action Sitessupporting
confidence: 65%
“…In the later life, these offspring may in turn suffer from impaired reproductive potential or lead to the failure in further reproduction. Among the various alterations in parents of fish during reproductive period, it has been suggested that induction of VTG in males, occurrence of intersex gonads and change of sexual behaviors were correlated with reproductive failure and proposed as biomarkers to indicate reproductive impairment (Jobling et al, 1998;Gronen et al, 1999;Cheek et al, 2001). However, in some other cases (Seki et al, 2002;Kang et al, 2002Kang et al, , 2003, induction of VTG and testis-ova does not necessarily predict reproductive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Vitellogenin is a yolk protein, which is scarcely present in male medaka, and is markedly induced by environmental estrogenic compounds (Gronen et al 1999, Shioda & Wakabayashi 2000. Exposure to 3 p.p.b.…”
Section: Exposure To Rhubarb Extract Increased Serum Vitellogenin Levmentioning
confidence: 99%